Case Report: Can preoperative implantation of veno-arterial extracorporeal membrane oxygenation lead to embolic events in infective endocarditis? - Li, Tianlong; Wu, Xiaoxiao; Chen, Tingrui; Pan, Chun; Yue, Ruiming; Xiang, Chunlin; Yu, Tao; Jiang, Zhenjie; Huang, Xiaobo; Tang, Xuemei; Wang, Yiping (Frontiers in Cardiovascular Medicine, 2024)
Early-stage infective endocarditis (IE) can lead to severe complications, including infarctions and metastatic infections caused by inflammatory embolus shedding. Common embolism sites include the brain, spleen, kidneys, lungs, and intestines. Additionally, acute heart failure (AHF) can occur in up to 40% of cases, and its presence can impact the clinical outcomes of patients with IE. Cardiogenic shock (CGS) is often more likely to occur after AHF has taken place. If bacteria invade the blood, infectious shock can occur. Patients with IE can experience simple CGS, septic shock, or a combination of the two. Extracorporeal membrane oxygenation (ECMO) typically serves as a Bridge for Heart failure and Cardiogenic shock. Previous research indicates that there are limited reports of ECMO support for patients with IE after CGS has occurred. Because CGS may occur at any time during IE treatment, it is important to understand the timing of ECMO auxiliary support and how to carry out comprehensive treatment after support. Timely treatment can help to reduce or avoid the occurrence of serious complications and improve the prognosis of patients with IE. Our work combines a case study to review the ECMO support of IE patients after CGS through a literature review. Overall, we suggest that when patients with IE have large bacterial thrombosis and a greater risk of shedding, it is recommended to carefully evaluate the indications and contraindications for ECMO after discussion by a multidisciplinary team (MDT). Still, active surgical treatment at an early stage is recommended.